The tasks of a nurse in care for a patient after breast augmentation surgery by the implant placement method - Weronika Nawłatyna; Paulina Myszka; Piotr Pawłowski; Klaudia Olga Jakubowska; Aneta Kościołek (Kazimierz Wielki University, 2019)
Introduction. Breast augmentation is an increasingly frequent surgical intervention performed in women. This medical procedure is performed in the operating theatre or treatment room under general anesthesia. The doctor makes an incision, creates a pocket in the breast tissue and places an implant. The cut is closed with surgical sutures. A breast augmentation procedure, like any surgical procedure, is associated with the risk of complications. A nurse as a member of a therapeutic team is obliged to provide the highest quality care, prevent complications and perform therapeutic, rehabilitative, educational, preventive and health promotion functions. Aim. The aim of the study is to determine the tasks of a nurse in caring for a patient after a breast augmentation procedure by the implant placement method. Methods and materials. The study was based on the case study method, the research techniques included an interview, nursing observation, measurement and a documentation analysis. The research tools used for the study included the Individual Nursing Care Card, the Visual Analogue Scale - VAS, risk of postoperative nausea and vomiting - the Apfel score. Findings. Nine nursing diagnoses based on the patient's health issues were made during the research process. Conclusions. The nursing problems of the patient after the breast augmentation procedure by the implant placement method result from the procedure itself and hospitalization.